ANALISIS KADAR SERAT DAN KADAR PROTEIN SERTA PENGARUH WAKTU SIMPAN TERHADAP SEREAL BERBASIS TEPUNG AMPAS KELAPA DAN TEPUNG TEMPE - Fitrianingsih Mozin; Nurhaeni; Ahmad Ridhay (KOVALEN: Jurnal Riset Kimia, 2019)
Research on dissolved protein and crude fiber flour based on coconut pulp and tempe flour has been performed. This study aims to determine the effect of shelf time on levels of dissolved protein and crude fiber flour-based cereal coconut pulp and tempeh flour. Cereals were made from coconut pulp flour and tempe flour as the main ingredients and the ratio of the ingredients was varied to 25:75; 50:50; and 75:25. The ratio of 25:75 produced the highest dissolved protein level of 3.88% and the 75:25 ratio produced the highest crude fiber of 21.96%. Keywords: Coconut pulp flour, tempe flour, dissolved protein, crude fiber